PENILAIAN RISIKO KESEHATAN LINGKUNGAN KECAMATAN ABIANSEMAL, KABUPATEN BADUNG - Lestari, Ni Ketut Sri; Wirawan, I Made Ady; Januraga, Pande Putu (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2021)
Environment, a variable that often gets special attention in assessing public health and environmental health, is an effort to prevent disease. Environmental Health Risk Assessment (EHRA) is a comprehensive study about sanitation facilities' conditions and risky behaviors on public health. Abiansemal District is one of the tourist destinations that has a very complex impact, especially on environmental health aspects. Behavior is a highly potential factor for health status, clean and healthy behavior is strongly influenced by the availability of sanitation facilities in order to control physical environmental factors that can harm health. This study determines the Health Risk Index and obtains an overview of the sanitation facilities condition and community behavior that has a risk for environmental health in Abiansemal District, Badung Regency. This study used stratified random sampling using a sample in the Abiansemal sub-district which has been determined as the target study area. Households to be visited in each village were selected randomly by stratified random sampling. After finding the first household visited, an interview was conducted according to the available questionnaire and after it was completed it was forwarded to neighbors until it found 40 houses per village. SPSS 20.0 is used for the data analysis. The description of sanitation facilities and community behavior that poses a risk to health in strata 1 has the main problem in domestic waste with the highest score of 36, while strata 2 has the main problem in solid waste with a score of 43 and strata 3 has the main problem in domestic wastewater with a score of 45. Analysis results of the sanitation risk index for the category of low risk/less risky area for strata 1 (1 village), the category of high-risk area for Strata 2 (11 villages), and the category of moderate risk area is in Strata 3 (6 villages). The high-risk area is found in Strata 2 (11 villages). Keywords: EHRA; Environmental health; Abiansemal; Badung.